A Nidānātmaka (Epidemiological) Study of Kuṣṭha (Skin diseases) among local community of Jaipur - Rao, Jogender; Godatwar, Pawan Kumar; Gavali, Preeti (International Research Journal of Ayurveda & Yoga, 2021)
Āyurveda is an oldest system of medicine practiced ini various parts of India and Indian sub continents. In today’s era due to lack of physical activity, altered food habits, pollution, chemical exposure, number of skin disease has increased. In Āyurveda classics skin diseases are described under ones broad term called kuṣṭha, which is further categorized into two major groups i.e. Mahākuṣṭha and Kṣudrakuṣṭha. The study aimed to find out the prevalence and nidāna of Kuṣṭha (Skin diseases) in the local community. A survey study was conducted at NIA O.P.D, I.P.D., Bombaywala hospital, Satellite hospital, and various camps in Jaipur. For this survey total 200 skin disease patients were taken and diagnosed as per Āyurvedika perspective and Psoriasis criteria. Observations of the study are presented in graph 1 to 12 according to various profile. Kuṣṭha mainly affects in middle age group as the busy schedule and faulty dietary habits might contribute in the pathogenesis of disease. The disease is chronic in nature and bear strong family history and is affected by mental stress. Vāta-Kapha Prakṛti is more prone to be affected by the disease and intake of excessive amount of lavaṇa ras may contribute in the disease formation or aggravation.